Metode Pengembangan Aspek Moral, Kognitif, dan Motorik pada Murid TK yang menerapkan Kurikulum Pendidikan Holistik Berbasis Karakter dan Kurikulum Berbasis Kompetensi - Ryandita, Maya (UI Scholars Hub, 2010)
The aim of this study is to describing how the moral, cognitive, and motoric aspects of development are carried out by the teacher through the implementation of different curriculum at 'X' Kindergarten and 'Y' Kindergarten, with qualitative methods and descriptive design. The result shows there are diversity of ways of development used by the teachers and there are advantages possessed X Kindergarten emphasis on the moral aspects of development, so allocate time specifically in that regard. Y' Kindergarten emphasis on the development of religious values and skills of reading, writing, and arithmetic, thus allocating more time and specific ways to develop such capabilities.